Jumlah Wajib Pajak, Penggunaan E-Filling dan Penyuluhan Perpajakan Serta Pengaruhnya Terhadap Penerimaan Pajak Penghasilan Wajib Pajak Orang Pribadi dengan di Moderasi Kepatuhan Pelaporan Pajak - Darwin M; Oktavia Marpaung (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The objective of this research is to examine the impact of the number of taxpayers, the use of e-filing, and tax education on the income tax revenue of individual taxpayers, moderated by tax reporting compliance. The study employs a quantitative data analysis approach using multiple regression analysis and path analysis. The data analyzed is sourced from the tax database from the years 2014 to 2022. The results show that the variables of the number of taxpayers and the use of e-filing have a significant and positive effect on tax revenue. However, the variable of individual taxpayer compliance does not have a significant impact on tax revenue. Furthermore, the moderating effect of individual taxpayer compliance ratio on the three independent variables does not significantly influence tax revenue.